Comparison of Treatment Methods for Carpal Tunnel Syndrome: Surgical vs. Non-Surgical - Szalajska, Julia; Wojcieszek, Maria; Wierzejska, Natalia; Domański, Mikołaj; Kopczyńska, Barbara; Czyżniewska, Oliwia; Czupryńska, Karolina; Otręba, Karina (Quality in Sport, 2024)
Introduction Carpal tunnel syndrome (CTS) is a common condition that results from the compression of the median nerve within the carpal tunnel in the wrist. Both surgical and non-surgical treatments are used to manage CTS. While surgery is necessary in some cases, many patients can be treated effectively with conservative methods. This review compares the efficacy of surgical treatment for CTS against various conservative approaches. Aim The study aims to evaluate and compare the outcomes of surgical versus conservative treatments for CTS, focusing on symptom relief, patient outcomes, and long-term prognosis. State of Knowledge The carpal tunnel is a narrow passage in the wrist formed by carpal bones and the flexor retinaculum. Compression of the median nerve within this tunnel leads to CTS, which can be caused by anatomical variations or systemic conditions like diabetes. Symptoms include pain, numbness, and tingling in the hand, which may worsen at night or with repetitive movements. Summary (Conclusions) Surgical treatment, especially decompression, offers superior symptom relief and functional improvement but carries risks of complications. Conservative treatments like wrist immobilization and anti-inflammatory medications are effective for many patients, supporting their use as initial treatment. Further research is needed to optimize CTS management.